The Effect of Instagram Information Quality on Consumer Purchase Intentions for Delivery Services - Aji Kresno Murti; Nalal Muna; Dandy Fitra Novalda (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the strategic role of Instagram in influencing consumer purchase intentions for international shipping services in Jakarta. The primary focus is on the quality of information conveyed through Instagram content and its impact on consumer buying interest. With the growing use of social media as a source of information and reference, this research aims to provide practical insights for international shipping service providers to optimize their content strategies. A quantitative approach was used by distributing a closed-ended questionnaire via Google Forms to 452 respondents in the Jakarta area. This method was chosen to ensure efficient distribution and ease of participation. The analysis results show that the quality of information delivered through Instagram including accuracy, relevance, and clarity of content significantly influences consumer purchase intentions. These findings highlight the importance of managing informative, engaging, and trustworthy content in digital marketing strategies, particularly on Instagram.